ENHANCING INTERCULTURAL COMPETENCE BY IMPLEMENTING DIGITAL STORIES INTO THE CLASSROOM - Alimova, M.H.; Abduvoxidova, H. M. (FAN va JAMIYAT, 2018)
The English language teaching aims to understand its importance and the value of this lingua franca, being the language instrument to give access to a globalized world. This article conveys new techniques of using technology in the EFL classroom. It provides some practical advice of implementing mini-digital stories into the classroom instruction. At the same time the focus is given to the understanding of cultural issues in intercultural settings.